Higher Education in 2040 : a global approach - Zwaan, Bert van der, 1952- (Online access: De Gruyter De Gruyter Open Books., 2017)
Since the Middle Ages, universities have displayed impressive resourcefulness in their ability to adapt to the changing dynamics and demands of their times. But in the last fifty years, the landscape of higher education - with the emergence of online and mass education, skyrocketing tuition, and a controversial system for ranking institutions - has begun evolving so rapidly and profoundly that the concept of the university now needs to be rethought. This book explores the future of modern higher education by looking at it on a global scale. Bert van der Zwaan compares European developments with those taking place in North America and Asia to argue that the phoenix of an entirely new type of university will rise from the ashes of the classical system: less tied to buildings and set locations, the new university will embed itself more deeply in society by offering innovative forms of digital knowledge and making customized teaching available on demand. A timely discussion of a topic whose worldwide impact continues to grow, this is essential reading for anyone concerned about the state of higher education - both for today's students and in the decades to come.